Street altars in the construction of the identify landscape: Magical neighborhood of Santa Julia, México City - Gallegos Navarrete, Blanca Margarita (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Santa Julia, in Mexico City, emerged at the beginning of the 20th century as a subdivision for the low-income population. In the past it acquired fame for being the place where one of the most renowned bandits of the Porfiriato period lived and was apprehended: “El Tigre de Santa Julia”. This fact led it to be considered as dangerous neighborhood. On the other hand, the religiosity of the population that lives there, it leads them to manifest themselves through street altars that today are tradition, as well as important urban-architectural references of the identity landscape of this area.